Constructing a novel mitochondrial-related gene signature for predicting survival and evaluating the tumor immune microenvironment in clear cell renal cell carcinoma - Qin, Jiaxuan; Zhang, Lijian; Chen, Bowen (Frontiers in Genetics, 2025)
BackgroundMitochondria play an important role in tumors. Cellular energy supply, signaling, metabolism, autophagy, aging, and tumorigenesis are all associated with mitochondria. However, we lack a reliable prognostic model using mitochondrial-related genes in clear cell renal cell carcinoma (ccRCC).MethodsA systematic analysis of available TCGA databases and related studies was conducted using the R language and online analysis tools to evaluate the prognostic value of mitochondrial-related genes and the tumor microenvironment in ccRCC.ResultsWe constructed a novel mitochondrial-related gene signature for predicting survival and evaluating the tumor immune microenvironment in ccRCC. The mitochondrial-related gene signature included MICALL2, FKBP10, and ACADSB. According to the risk score of the risk model, ccRCC patients were divided into high- or low-risk groups. The ccRCC high-risk group with a high-risk score is related to poor prognosis and poor efficacy from immune checkpoint inhibitors (ICIs).ConclusionOur mitochondrial-related gene signature, as a risk model, could be a reliable ccRCC prognostic biomarker and could predict the response to immunotherapy. The risk score was correlated with the tumor microenvironment and immune cell infiltration.